Surface organisation and transistor action in naphthalocyanine and porphyrin nanoring thin films - Esmail, Ayad M. S. (2017)
In this thesis, the growth of metal-free naphthalocyanine (Nc) and copper naphthalocyanine (CuNc) on both bare Si/SiO2 and octadecyltrichlorosilane (OTS) modified Si/SiO2 surface were studied. The effects of the substrate temperature on morphology and structure of Nc and CuNc thin film growth were presented. For these purposes thin films of Nc and CuNc prepared by thermal vacuum evaporation were studied using atomic force microscopy (AFM) and X-ray diffraction (XRD). We observed that the increase of substrate temperature during growth affects the morphology, preferential molecular orientation and degree of crystallinity of both Nc and CuNc thin film, which were used as active layers in organic field effect transistor (OFET) devices. Organic thin film transistors (OFETs) were fabricated using these molecules as the active layers and their electrical characteristics were measured under both vacuum and atmospheric conditions and they were found to exhibit p-type transistor action. A series of samples of the Nc and CuNc thin films were grown on Si/SiO2 and OTS-modified oxide surface at different substrate temperature but fixed equivalent deposited thickness. The growth conditions, particularly the substrate temperature strongly affect nucleation size and shape of the organic thin film. In general, the thin film morphology shows a near circular grain and elongated grain shape at low substrate temperature, while the thin Nc film shows small needle-like structure and extended needle-like crystalline structures with large gaps at high substrate temperature. The optimum substrate temperature during the growth of Nc on both surfaces is achieved at 200 °C, and this occurs for growth of CuNc at 180 °C and 160 °C on Si/SiO2 and OTS surfaces, respectively, for which the naphthalocyanine thin film shows the best morphological and electrical properties. We used Nc and CuNc thin films prepared at different substrate temperatures as active layers to fabricate bottom and top-contact organic field effect transistors. Their electrical characteristics were measured at room temperature in vacuum and air in the dark. We plotted the output characteristic and transfer characteristic of all OFET devices so that the effects of grain size and crystal structure on the performance characteristic of Nc OFET device could be investigated. Then we studied the effects of hysteresis and charge traps on device performance when exposed to air. We found that the changes generated by exposure of the device to atmosphere may be reversed by annealing the thin film to ∼100 °C in vacuum. We reported the highest mobility of (5.16 ± 0.23) × 10-2 cm2 /Vs for top-contact Nc device prepared at 200ºC on SiO2 after annealing in vacuum, and also we reported the highest mobility of (3.56 ± 0.14) × 10-2 cm2 /Vs for top-contact CuNc device prepared at 180ºC on SiO2 after annealing in vacuum. We found that the top-contact device always performs better than the bottom-contact device. We attributed this to the change of morphology of active layer in the interface between contact metal and SiO2. Solvent induced self-assembly, self-trapping, and self-organizing of c-P30 cyclic porphyrin polymers on the Au surface that are deposited from two solutions and various concentrations in ambient condition was also studied. This results in the arrangement of cyclic polymers in different configurations such as stacking columnar, supramolecular nesting and uniform height hexagonal close packed structure. These conformations are observed using scanning tunnelling microscopy. Highly covered surface stacking columnar like porous array is also observed. We show that toluene:methanol mixture can play a crucial role in self-assembly of supramolecular structure in two dimensions, π-π stacking conformation perpendicular over surface in three dimensions and single in double nested nanoring conformation. Cyclic porphyrin polymers deposited from toluene shows nested nanorings structure, such as single nanoring self-trapped inside a near-circular shape single ring on surface. Diluted solutions using a large volume of methanol relative to the toluene can suppress the adsorption of nanorings to the surface. Interestingly, adsorption of the cyclic polymer from toluene:methanol 3:5 can result in the formation of uniformly height hexagonal close packing on surface, where nanorings aggregate as columnar stacks in two layers, dependent on concentration. Our results show that the self-assembly of artificial cyclic polymers is dependent on solvent and concentration provides a significant step towards control of the three-dimensional arrangement of supramolecular conformation on surfaces using non-covalent interactions.